Resilience Development with Digital and Fintech-Based to Improve Business Sustainability: A Conceptual Model - Winarsih WINARSIH; Khoirul FUAD; Hendri SETYAWAN (Communications of International Proceedings, 2021)
The small and medium enterprises (SMEs) sector is one of the main pillars of the national economy. Amid the corona virus pandemic (Covid-19), the sector's resilience, which absorbs millions of workers has decreased drastically. For industry players, especially SME actors must adapt to new conditions and behavior (new normal) and implement social distancing. One way is by developing the self-resilience of the business to survive and transform so that the business can be run from a downturn. Resilience is the capacity to minimize losses when an economic hit occurs to recover quickly. As part of the digital economic ecosystem, SMEs can provide opportunities for transformation and innovation, including in the field of financial technology (fintech). It requires knowledge of digital skills relevant to the business. In addition, monitoring and transparency of traces of digital and real-time use of money are also carried out so that business sustainability can be maintained.
Keywords: Resilience based on Digital Transformation; Fintech; Business Sustainability